Chemical Feedstock Recovery via the Pyrolysis of Electronically Heated Tobacco Wastes - Yejin Choi (MDPI AG, 2021)
The pyrolysis of waste electronically heated tobacco (EHT), consisting of tobacco leaves (TL), a poly-lactic acid (PLA) filter, and a cellulose acetate (CA) filter, was investigated using thermogravimetric (TG) and pyrolyzer–gas chromatography/mass spectrometry (Py-GC/MS) analysis. The pyrolytic properties of waste EHT obtained after smoking were comparable to those of fresh EHT. Although the maximum decomposition temperatures (TmaxS) of waste TL and CA were similar to those of fresh EHT components, the Tmax of waste PLA was slightly higher than that of fresh PLA due to smoldering. The Tmaxs of PLA and CA were lowered when they were co-pyrolyzed with TL due to interactions between pyrolysis intermediates. The apparent activation energies for the non-isothermal pyrolysis of waste EHT components were higher than those of fresh EHT components. Py-GC/MS analysis results indicated that considerable amounts of chemical feedstocks, such as nicotine and limonene from TL, caprolactone and lactide from PLA, and acetic acid and triacetin from CA, can be recovered by simple pyrolysis of EHT. Co-pyrolysis of TL, PLA, and CA revealed that the experimental amount of lactide was much larger than the calculated value, suggesting its synergistic formation.